The materiality of mourning
1 online resource (280 pages)
Keywords: Tangible remains play an important role in our relationships with the dead; they are pivotal to how we remember, mourn and grieve. The chapters in this volume analyse a diverse range of objects and their role in the processes of grief and mourning, with contributions by scholars in anthropology, history, fashion, thanatology, religious studies, archaeology, classics, sociology, and political science. The book brings together consideration of emotions, memory and material agency to inform a deeper understanding of the specific roles played by objects in funerary contexts across historical and contemporary societies.